An Incrase In Skills Concluded Text Reading Trough Model Cooperative Integreted Reading and Composition - Zulaekha Zulaekha (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this research to increase reading text that concluded with the reading integreted learning cooperation and composition in charge subject of Indonesian language in primary school class I. research is by research the act of class (PTK) as much as the, with every consisting of planning, observation and reflection. The meeting test done by post, 1 in students completed 2 reached 90 % this shows that cooperation learning model reading integreted and composition can improve learning outcomes especially charge students subject of Indonesian language class 1 at SDN Kalirejo 03